Solutions: 1. False; the solutions are imaginary because inside of the square root is a (-) sign. 2.

True; x^2=27 can be solved using the square root property. 3. x= -2 and 2; 4x^2 = 16. First divide both sides by 4 then you get x^2 = 4. Then square root both sides to get rid of the square, you get: x=+/-√4. the answer is x = -2 and 2 4. √3 / 3; 1 / √3. First you multiply the top and bottom by √3 and you get √3 / 3. That's your final answer. 5. 2√7; 14 / √7. First you multiply both sides by √7 and you get 14√7 / 7. Then to reduce you divide like terms by 7 and get 2√7, whichj is your final answer. 6.x = 4 and 0; (x-2)^2 = 4 Find the square root from both sides of the equation. √[(x-2)^2] = √4 x - 2 = ±2 Decide if you are going to use plus or minus the 2 on the left side of the equation. Let’s use positive 2. Add 2 to both sides. x-2=2 +2 +2 x= 4 The first solution is 4. Because there is a plus or minus symbol, you must solve the equation twice as if the negative number was used rather than the positive. x - 2 =-2 Add 2 to both sides like in the first equation. x - 2 = -2 +2 +2 x=0

The second solution is 0. The answer to this question is x= 4 and x=0. 7.11√3; 3√27-√12+√48 First, you must simplify each radical. 3√27 becomes 9√3. √12 simplifies to 2√3. √48 simplifies to 4√3. The new problem looks like this: 9√3 - 2√3 + 4√3 Add or subtract all the numbers OUTSIDE the radicals. This equals 11. √3 does not change. The solution is 11√3. 8. 1; (√3-√2)(√3+√2) Use the FOIL method. Multiply √3 by √3 and √2. 3 + √6 Then multiply -√2 by √3 and √2. -√(6) - √(4) Put it together to get 3 +√6 - √6 -√4. √6 - √6 cancel each other out. You are left with 3 - √4. The square root of √4 is 2. You are left with: 3-2 Subtract to get 1. 9. x = -2i and 2i; x^2 = -4 Find the square root of x^2 and -4. √(x^2) = √-4 Finding the square root of a negative results in the use of the variable i. x = ±2i. It can also be written -2i and 2i. 10. x = √6 / 2 and -√6 / 2; 7x^2 + 3 = -x^2 + 15 First, add -x^2 to both sides of the equation. 7x^2 + 3 = -x^2 + 15 + x^2 +x^2 8x^2 + 3 = 15 Subtract 3. 8x^2 + 3 = 15

-3 -3 8x^2 = 12 Divide 12 by 8 to separate it from the x^2. (8x^2)/8 = 12/8 x^2 = 12/8 Find the square root for both sides. √(x^2) = √(12/8) x = √(12/8) Simplify the fraction. x = √(3/2)

11. +/-2.1875=t Plug in 35 for “h0” and 0 for “h”: 0=-16t^2 + 35 Subtract 35 from both sides. -35 = -16t^2 Divide -16 from both sides leaving the t^2 on the right side. -35/-16 = t^2 Get the square root of both sides. (√35/16) = (√t^2) ±2.1875 = t The positive answer must be used because time cannot be measured in negative seconds.